The relationship between the competence and performance of family planning instructors in family assistance at risk of stunting in Lampung province - Dian U.P. Putri; Trias Mahmudiono; Diah Indriani; Biyanti Lisatriana (Journal of Public Health in Africa, 2023)
Introduction. A national action plan for the acceleration of stunting reduction was prepared to encourage and strengthen convergence between programs through a stunting-risk family approach. The increasing role of Family Planning Instructors in assisting families at risk of stunting becomes a challenge to support behavioral change in the community.